Evaluation of sepsis teaching for medical and dental students at a British University. (22nd June 2021) - Ali, Kamran; Venkatasami, Neelam; Zahra, Daniel; Brookes, Zoe; Kisielewska, Jolanta
Abstract: Introduction: The aim of this study was to evaluate sepsis on undergraduate programmes in medicine (BMBS), dentistry (BDS) and dental therapy (BScDTH) at a university in England. Materials and Methods: The study was carried out at the Faculty of Health, University of Plymouth. Questionnaires consisting of a series of closed and open‐ended items were designed for students and faculty by a group of academics. Following a pilot, participants were invited to complete the questionnaires online. Data collection and analyses were completed over a period of 3 months. Results: A total of 71 students responded, including 43 were on the BDS programme, 21 on BMBS and 7 on BScDTH. The vast majority were aged between 18–24 years old ( n  = 61), with 9 reporting being between 25–44 years old. Of the 14 staff who responded, 13 were aged between 35 and 54 years old, with one respondent reporting being aged 25–34. The participants reported their perceptions regarding the teaching and clinical exposure of students to sepsis patients; availability of resources for students and patients to raise sepsis awareness. Students across all programmes reported limited clinical exposure to management of sepsis and lack of confidence in recognising early signs of sepsis in patients. The agreement profile between programmes only differed significantly for recognition of sepsis risk item ( χ (6, n  = 71) = 26.187, p  < 0.001), with BDS students disagreeing with the item to a larger extent than BMBS and BScDTH students. Students and staff reported similar perceptions regarding information available to students and patients. Responses to open‐ended items provided several suggestions for improvements in the teaching of students and raising public awareness on sepsis. Conclusion: This study identified several areas related to sepsis teaching which require improvements across all programmes. The key issues highlighted by the students included limited clinical exposure to sepsis patients and lack of confidence in recognising early signs of sepsis.